A Reappraisal of Trade Deficit and Income Inequality in the United States, 1985-2007. - Thompson, Chris (My University, 2009)
The recent resurgence of income inequality in the United States has spawned a wide-ranging discussion to its causes, which has often focused on America's historically high trade deficit in the past two decades. Our project revisits this issue by investigating the latest trends in the U.S. income disparity from 1985 to 2007, and systematically examining the factors that might have influenced the income inequality.
Color poster with text, tables, and graphs.
Keywords: Balance of trade--United States; Income distribution--United States; Income distribution--Longitudinal studies; Posters